AVALIAÇÃO DA EXPOSIÇÃO AO TRIBUTILESTANHO NOS PARÂMETROS MORFOLÓGICOS E METABÓLICOS EM RATOS EXPOSTOS AO FRIO - Merlo, Eduardo (2022)
Tributyltin (TBT) chloride is an endocrine-disrupting chemical linked with several metabolic complications. Brown adipose tissue (BAT) is emerging as a therapeutic target for metabolic complications. However, few studies have evaluated the TBT effect on BAT function. This study assessed whether a TBT exposure (100 ng/kg/day for 15 days via gavage) could modulate BAT morphophysiology. We evaluated the BAT parameters at room temperature (23ºC) and after a cold tolerance test (CTT – 6ºC) conditions. Interestingly, were observed low T4 levels in TBT rats under normal temperatures. A reduction in body temperature was observed in both conditions in TBT rats, suggesting an abnormal thermogenic function. BAT morphology irregularities were observed in TBT rats. Specifically, an increase in BAT lipid accumulation and unilocular adipocyte number. TBT also reduced lipid droplets and multilocular adipocyte number at room temperature. All these parameters were opposite in the CTT condition. Inflammation signals were observed in the TBT BAT. Collagen accumulation in TAM increased in the ambient condition, exacerbating in the cold condition in TBT rats. ROS production increased under both conditions. Finally, we observed negative correlations between body temperature and BAT lipid accumulation, BAT lipid accumulation and T4 levels, and multilocular adipocyte number. Conversely, and positive correlation was observed between BAT lipid accumulation, inflammation, and ROS production. Thus, these data suggest that the subacute and low dose of TBT exposure impaired BAT morphophysiology linked with lipid accumulation, inflammation, fibrosis, and oxidative stress in male rats.